Forensic examination of anonymous handwritten documents in order to obtain data on the identity of their author and performer - Bakhteev, Dmitry V.; Antropov, Alexey V. (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The anonymous document as an object of forensic research has an information field that is subject to study by three groups of scientific disciplines: handwriting, technical research of documents and forensic linguistics. Stability and reproducibility characteristics of handwriting and written speech allows us to identify the author and performer of an anonymous message, as demonstrated by the example of the authorsʼ practice.
Keywords: dokument odręczny; badanie pisma ręcznego; egzamin językowy; anonim